"The Serious Business of Arts and the Humanities" (AmeriQuests, 2012)
The continuing crisis in the humanities and the arts has affected funding and demands novel approaches. Using business techniques to facilitate the production and dissemination of the arts and the humanities in a university setting can be risky. This article discusses approaches that have proved to be successful.